Molecular epidemiology of human adenoviruses in children with and without respiratory symptoms: Preliminary findings from a case-control study - Sevrin Zadheidar; Jila Yavarian; Zahra Heydarifard; Ahmad Nejati; Kaveh Sadeghi; Nastaran Ghavami; Simin Abbasi; Somayeh Shatizadeh Malekshahi; Talat Mokhtari-Azad; Nazanin-Zahra S (BMC, 2022)
Abstract Background Human adenovirus (HAdV) is an important viral agent in children which can lead to severe acute respiratory infection (SARI). Reports on molecular epidemiology of HAdVs in Iran are limited. This case-control study is conducted to compare the HAdV infection rate and molecular epidemiology among two groups of children with and without respiratory symptoms in Tehran, Iran during 2018-2019. Methods Nested PCR was performed on 120 oropharyngeal swabs taken from children aged five and younger with SARI who were hospitalized as the case group, and 120 oropharyngeal swabs were collected from children of the same age without respiratory symptoms as the control group. For positive samples Sanger sequencing was done and a phylogenetic tree was drawn afterward. Results Out of 120 cases, 8 (6.6%) tested positive for eachHAdV types including 6 (75%) HAdV-B7, 1 (12.5%) HAdV-C2, and 1 (12.5%) HAdV-C6. Among the control group, out of 120 samples, 8 (6.6%) were positive comprising 5 (62.5%) HAdV-C5, 2 (25%) HAdV-F41, and 1 (12.5%) HAdV-C6. Conclusion The present study indicated a different viewpoint of HAdV molecular epidemiology in which the genotypes were compared in children with and without respiratory symptoms. HAdV prevalence was equally common in cases and controls but different genotypes were detected in these two groups. HAdV-B7 was the main type among children with SARI, dissimilar to children with no respiratory symptoms where HAdV-C5 was the predominant type. Detecting HAdV-F in oropharyngeal swabs was a rare finding, which requires further investigation.